Emerging source of infection – Mycobacterium tuberculosis in rescue dogs: a case report. Issue 11 (7th November 2020) - Mentula, Silja; Karkamo, Veera; Skrzypczak, Teresa; Seppänen, Jaana; Hyyryläinen, Hanne-Leena; Haanperä, Marjo; Soini, Hanna
Abstract : Rescue dog activity is a heavily increasing form of dog charity. Imported homeless dogs represent a reservoir of zoonotic diseases putting owners, veterinarians and pathologists repeatedly at risk. The clinical signs of tuberculosis in a dog are non-specific and diagnosis is often delayed or dismissed. We present a case of 9 months of possible exposure at home and definite exposure at laparotomy and autopsy to intestinal tuberculosis in a family dog imported from Romania to Finland. Persistent gastrointestinal symptoms started 2 years after the import. Abdominal pain, diarrhoea and vomiting proceeded and led to spontaneous death. Mycobacterium tuberculosis was identified in the liver, lymph nodes and intestine at autopsy. Exposed persons were notified and follow-up was provided, and no further infections were identified within 12 months of follow-up. The heavily increasing import of companion animals presents unexpected public health risks, such as prolonged exposure to tuberculosis, of which the general public is not aware. The dramatic consequences and high costs of tuberculosis could be reduced through accessible information of the risks of imported animals to both the general public and veterinarians, in addition to availability of rapid diagnostics and proper personal protection.